Green Revolution and Food Security in India: A Review - Yadav, Shikha; Anand, Subhash (National Geographical Journal of India, 2022)
India suffered from food shortage with occasional drought, famines which compelled to import. A rapidly growing population was creating more and more pressure on the agriculture sector and the country was suffering from lack of food grains in 1950. That time population was more, and food production and productivity were less. The Green Revolution which has helped in boosting self-confidence in our agricultural capability and balance between population growth and food grains production. The most remarkable achievement of the Green Revolution is the significant increase in the production of two major crops, rice and wheat. This first Green Revolution recorded both positive and negative implications on society and the environment. Present impacts are very alarming for human health. In spite of the huge agricultural production, there are some questions about the status of food security in the country. There is dire need to frame the second Green Revolution for the country. The intensification and food production diversification by promoting and providing a nutrient-dense improved variety of seeds of predominant crops are needed. This paper reviews the features of agricultural policies and the impact of the initial phase of the Green Revolution, and food security challenges in India